SPORT SPECIALIZATION, ATHLETIC IDENTITY, AND COPING STRATEGIES IN YOUNG ATHLETES. Issue 7 (30th July 2021) - Christino, Melissa A.; Coene, Ryan P.; O'Neil, Madeline; Daley, Mary; Williams, Kathryn A.; Ackerman, Kathryn E.; Kramer, Dennis E.; Stracciolini, Andrea
Background: Child and adolescent sports participation continues to rise, often with specialization in a single sport at an early age. Psychological associations with sport specialization have been reported, although targeted research is lacking. Hypothesis/Purpose: The purpose of this study was to examine associations between sport specialization, levels of athletic identity, and coping skills among adolescent athletes. Methods: A cross-sectional survey study of sports medicine patients, 12-18 years, was performed. Athletes completed a one-time, voluntary, anonymous survey. Surveys included demographics, sport participation information, Athletic Identity Measurement Scale (AIMS, 10-item, range 7-70), Jayanthi Sport Specialization Scale (range 0-6), and Athletic Coping Skills Inventory (ACSI, 7 subscales, range 0-84). Statistical analysis included Fisher's exact tests, t-tests, Pearson correlations, and linear regression. Results: 334 out of 430 eligible patients completed surveys, with a response rate of 78%. Mean age was 15.0±1.8 years and participants were 64.6% female. 97.7% of participants designated participation in a primary sport, where they spent most of their time. Athletes reported starting this primary sport at a mean age of 7.2±3.7 years. Using the Jayanthi scale, 52.1% of respondents were classified as low specialization (score 0-3) and 47.9% as highly specialized (score 4-6). Sport specialization patterns did not significantly differ by age, sex, or sport. AIMS and Jayanthi scores positively correlated (r=0.39, p<0.0001), and athletes with the highest athletic identities (top 25%) were significantly more specialized than those with the weakest (bottom 25%) athletic identities (4.1 vs 2.5, p<0.001). Regression analysis demonstrated that every 1 point increase in the Jayanthi specialization scale was associated with an AIMS score increase of 2.7 points (p<0.001). The AIMS score also increased 0.83 points for every one month increase in playing their primary sport (p<0.001), and decreased 0.42 points with each year delay in starting their primary sport (p=0.02). Highly specialized athletes had significantly higher overall coping skills scores compared to low specialization athletes (51.6 vs 48.4, p<0.02), particularly on ACSI subscales of Coachability, Concentration, Confidence & Achievement Motivation, and Goal Setting & Mental Preparation (Table 1), however highly specialized athletes reported less Freedom From Worry compared to those with less specialization (5.8 vs 6.7, p=0.02). Conclusion: Athletic identity was higher in athletes who were more specialized and started their primary sport earlier in life. Greater sport specialization may confer some advantages in developing coping strategies in young athletes, however these athletes may be at risk for more worry compared to less specialized athletes. :